Quality of Health Services at Muara Tiga Village Health Center, Mulak Ulu District, Lahat District - Ela Peranika; Ike Apriani; Muhammad Anshori DM (Gayaku Publisher, 2022)
This study entitled Quality of Health Services at the Muara Tiga Village Health Center, Mulak Ulu District, Lahat District. The purpose of this study was to determine the quality of health services at the Muara Tiga Village Health Center, Mulak Ulu District, Lahat Regency referring to Zeithaml's theory in Ratminto and Winarsih (2005:175-176), which states that to evaluate the quality of public services, people generally use five ( 5) dimensions, namely reliability (reliability), responsiveness (responsiveness), assurance (guarantee), empathy (empathy), and tangible (physical evidence). This study uses a qualitative descriptive research type with inductive data analysis and uses research informants consisting of functional officials assigned to provide services at the Muara Tiga Village Health Center; administrative staff at the Muara Tiga Village Health Center; and community users of health services at the Muara Tiga Village Health Center as primary data sources. The technique used by researchers is descriptive data analysis, with the results of the study showing that: (1) The quality of health services at the Muara Tiga Village Health Center seen from the dimensions of reliability, responsiveness, assurance, empathy, and physical evidence is under community expectations.